PENGARUH PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN DENGAN LOYALITAS SEBAGAI VARIABEL INTERVENING - Ayu Rahmadani; Zulkarnain Nasution; Meisa Nasution (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Laundry business is one of the fastest growing businesses in Rantauprapat-Labuhanbatu region. The number of competitors causes the importance of getting loyal customers towards laundry. Satisfaction can be affected by quality of service, trust and consumer loyalty. This research aims to determine the influence of service quality, trust and loyalty on consumer satisfaction. Data analysis tool in this study is SPSS.22 to determine the effect between variables. The results of this study indicate that the quality of service has a significant positive effect on consumer satisfaction, trust has a significant positive effect on consumer satisfaction, loyalty has a significant positive effect on loyalty, trust has a significant positive effect on loyalty, service quality and trust have a significant positive effect on loyalty. Quality of service and trust has a significant positive effect on consumer satisfaction with customer loyalty as an intervening variable. The managerial implication of the research results is that Nazwa Laundry must be focused on quality of service and trust to achieve customer satisfaction and loyalty Keywords: Quality of Service, Trust, Customer Satisfaction, Loyalty